Core skills for world-level table tennis competition - Wu, T. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
In the world-level competition, the coaching staff helps athletes develop the essential strengths to excel at the highest level. The strengths are acquired from systematic training to enable athletes with the skills to understand the competition from the physical, technical, and mental perspectives to gain advantages over his/her opponents. In this research, we analysed team China`s coaching culture from 2002 to 2014 under the head coach Liu Guoliang. We aimed to derive the key elements of team China`s training philosophy, learned from their own success and failure in Olympics and World Championships games. Significantly, our analysis led to ten core skills/abilities to focus on. They are: (1) the physical strength and durability, (2) fundamentally sound techniques for steady performance, (3) ability to adjust and execute in-game strategies, (4) right attitude while facing challenges in competition, (5) ability to control the flow/tempo in competition, (6) awareness of the in-game transitions and opponent`s strategy, (7) mental strength to compete while trailing behind, (8) skill of in-game analysis, (9) big game experience, and (10) flexibility to integrate with team training/conditioning to peak for tournament. These ten points can serve as the training guidelines for coaches and athletes in preparation for the world-level competition.